Examining policy intentions and actual implementation practices: How organizational factors influence health management information systems in Uttar Pradesh, India. (October 2021) - Meghani, Ankita; Rodríguez, Daniela C.; Bilal, Huzaifa; Tripathi, Anand B.; Namasivayam, Vasanthakumar; Prakash, Ravi; Peters, David H.; Bennett, Sara
Abstract: This study investigates the implementation of a recent health management information systems (HMIS) policy reform in Uttar Pradesh, India, which aims to improve the quality and use of HMIS data in decision-making. Through in-depth interviews, meeting observations and a policy document review, this study sought to capture the experiences of district-level staff (street-level bureaucrats) who were responsible for HMIS policy implementation. Findings revealed that issues of weak HMIS implementation were partly due to human resources shortages both in number and technical skill. Delays in recruitment and the presence of inactive staff overburdened existing staff and weakened the implementation of HMIS activities at the block- and district-levels. District staff also explained how inadequate computer literacy and limited technical understanding further contributed to low HMIS data quality. The organizational culture was even more constraining: working within a very rigid and hierarchical organization was challenging for district data staff, who were expected to manage day-to-day HMIS activities, but lacked the discretion and authority to do so effectively. Consequently, they had to escalate minor issues to district leadership for action and were expected to follow their supervisors' directives– even if they contradicted HMIS policy guidelines. High performance pressures associated with achieving top district rankings deviated focus away from HMIS data quality issues. Many district-level respondents described their superiors' "fixation" with becoming a top-ranking district often resulted in disregard for the quality of data informing district rankings. Furthermore, the review of district rankings only partially encouraged district-level leadership to investigate reasons for low-performing indicators. Instead, low district rankings often resulted in punitive action. The study recommends the importance of incorporating the perspectives of district staff, and recognizing their discretion, and authority when designing policy implementation processes, and finally concludes with potential strategies for strengthening the current HMIS policy reform. Highlights: Well-designed policies are insufficient for successful HMIS policy implementation. Attention needs to be paid to organizational cultural factors. Strict organizational hierarchy and punitive work culture weaken HMIS implementation. Incorporating perspectives of policy implementers is critical for HMIS policy design.